Lateral Antebrachial Cutaneous Nerve as a Donor Source for Digital Nerve Grafting: A Concept Revisited - CANSÜ, CENGİZ EREN; ŞİRİN, EVRİM (My University, 2017)
Objective: The main objective of this study is to evaluate the availability of lateral antebrachial cutaneous nerve (LACN) autograft for acute or delayed repair of segmented digital nerve injuries. Patients and Methods: 13 digital nerve defects of 11 patients; treated with interposition of LACN graft that harvested from ipsilateral extremity were included in the study. Mean follow up period was 35, 7 months. The mean time from injury to grafting is 53, 3 days. The results of the mean 2PDT and SWMT values of injured /uninjured finger at the end of follow up period were evaluated with Paired T test. The correlation between the defect length and the difference of 2PDT, SWMT values between the uninjured and injured finger at the end of follow up period; were evaluated with Pearson - correlation analysis. Results: The mean value of our 2PDT and SWMT results are ~5,923, ~3, 52, respectively in which can be interpreted between the normal and diminished light touch. The defect length and difference percentage of SWMT values is positively and significantly correlated statistically. Mean length of interposed nerve grafts was 18.5 mm. The age of the patient and the mean values of 2PDT and SWMT with the difference % of 2PDT and % of SWMT are not statistically correlated. Conclusion: Based on results regarding sensory regaining at recipient side and negligible sensory deficit at harvesting side, we suggest that lateral antebrachial cutaneous nerve might be a valuable graft option for digital nerve defects.
Keywords: Autografting; Cutaneous nerve (LACN); Digital nerve injury; Donor source; Lateral antebrachial; Nerve grafting